Cryo‐electron microscopy of extracellular vesicles in fresh plasma. Issue 1 (31st December 2013) - Yuana, Yuana; Koning, Roman I.; Kuil, Maxim E.; Rensen, Patrick C. N.; Koster, Abraham J.; Bertina, Rogier M; Osanto, Susanne
Abstract : Introduction: Extracellular vesicles (EV) are phospholipid bilayer‐enclosed vesicles recognized as new mediators in intercellular communication and potential biomarkers of disease. They are found in many body fluids and mainly studied in fractions isolated from blood plasma in view of their potential in medicine. Due to the limitations of available analytical methods, morphological information on EV in fresh plasma is still rather limited. Objectives: To image EV and determine the morphology, structure and size distribution in fresh plasma by cryo‐electron microscopy (cryo‐EM). Methods: Fresh citrate‐ and ethylenediaminetetraacetic acid (EDTA)‐anticoagulated plasma or EV isolated from these plasmas were rapidly cryo‐immobilized by vitrification and visualized by cryo‐EM. Results: EV isolated from fresh plasma were highly heterogeneous in morphology and size and mostly contain a discernible lipid bilayer (lipid vesicles). In fresh plasma there were 2 types of particles with a median diameter of 30 nm (25–260 nm). The majority of these particles are electron dense particles which most likely represent lipoproteins. The minority are lipid vesicles, either electron dense or electron lucent, which most likely represent EV. Lipid vesicles were occasionally observed in close proximity of platelets in citrate and EDTA‐anticoagulated platelet‐rich plasma. Cryo‐electron tomography (cryo‐ET) was employed to determine the 3D structure of platelet secretory granules. Conclusions: Cryo‐EM is a powerful technique that enables the characterization of EV in fresh plasma revealing structural details and considerable morphological heterogeneity. Only a small proportion of the submicron structures in fresh plasma are lipid vesicles representing EV.